PENGARUH PELATIHAN DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT. HORIZON GROUP (HG) PONDOK BATU TAPANULI TENGAH - Sartika Febriyanti Tanjung; Mhd.Shafwan Koto; Rahmadiah Hanum (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
He formulation of the problem in this study is the effect of training and discipline on employee performance at PT. Horizon Group (HG) Pondok Batu, Central Tapanuli Regency This study aims to determine the effect of training and discipline on employee performance at PT. Horizon Group (HG) Pondok Batu, Central Tapanuli Regency. The sample in this study were employees of PT. Horizon Group (HG) Pondok Batu, Central Tapanuli Regency, totaling 26 (twenty six) people. The data analysis technique in this study is Multiple Linear Regression. The results of this study indicate: Partial training has a positive and significant effect on employee performance; Work discipline partially has a positive and significant effect on employee performance; Training and work discipline simultaneously have a positive and significant effect on employee performance